Mengkaji stail nyanyian Saloma daripada perspektif teknik vokal klasikal barat: Penggunaan vokal register / Nur Fardilla Nadia Abu Bakar - Nur Fardilla Nadia , Abu Bakar (2018)
Western classical singing techniques are often used by singers, bicyclists, classical and romantic singers in presenting works from famous times composers such as Mozart, Puccini and Schubert. It is used by singers who have knowledge in western classical singing techniques. While western censorship is synonymous in baroque, classical and romantic environments, researcher feels that this technique can be used in other music genres. Therefore, this thesis was written to study Saloma singing style from the perspective of western classical technique in the use of vocal register. This study will use a qualitative method approach where the researcher will study several songs sung by Saloma. These songs will be examined from the perspective of registering vowel usage and see how far the registration vocals are used. This study also shows that Western classical vocal techniques can be used as an alternative to a pop and classical singer in delivering Saloma songs. Researcher also argue that using this technique, a singer can produce the Saloma song-singing style well and it can also help with the difficulty of singing. The findings of this study can be used as a guide to vocal singers, students and teachers who want to apply this technique in singing Saloma songs even though this technique is more synonymous with western classical song singing, it can also be used in singing songs from a musical genre that others.